Examining Interpretations of Graphic Cigarette Warning Labels Among U.S. Youth and Adults. Issue 8 (2nd August 2016) - McQueen, Amy; Waters, Erika A.; Kaphingst, Kimberly A.; Caburnay, Charlene A.; Sanders Thompson, Vetta L.; Boyum, Sonia; Kreuter, Matthew W.
Abstract : Few studies have examined how diverse populations interpret warning labels. This study examined interpretations of 9 graphic cigarette warning labels (image plus text) proposed by the U.S. Food and Drug Administration among a convenience sample of youth (ages 13–17) and adults (18+) across the United States. Participants ( N  = 1, 571) completed a cross-sectional survey. Participants were asked to select 1 of 3 plausible interpretations (1 preferred vs. 2 alternative) created by the research team about the particular consequence of smoking addressed in each warning label. Participants also rated each label for novelty, counterarguing, perceived effectiveness, and harm. Smokers reported their thoughts of quitting, self-efficacy, and motivation to quit. Although at least 70% of the sample chose the preferred interpretation for 7 of 9 labels, only 13% of participants chose all 9 preferred interpretations. The odds of selecting the preferred interpretation were lower among African Americans, among those with less education, and for labels perceived as being more novel. Smokers reported greater counterarguing and less perceived effectiveness and harms than nonsmokers, but results were not consistent across all labels and interpretations. The alternative interpretations of cigarette warning labels were associated with lower perceived effectiveness and lower perceived harms of smoking, both of which are important for motivating quit attempts.